2021
DOI: 10.1038/s41467-021-21940-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GPR37 in macrophages confers protection against infection-induced sepsis and pain-like behaviour in mice

Abstract: GPR37 was discovered more than two decades ago, but its biological functions remain poorly understood. Here we report a protective role of GPR37 in multiple models of infection and sepsis. Mice lacking Gpr37 exhibited increased death and/or hypothermia following challenge by lipopolysaccharide (LPS), Listeria bacteria, and the mouse malaria parasite Plasmodium berghei. Sepsis induced by LPS and Listeria in wild-type mice is protected by artesunate (ARU) and neuroprotectin D1 (NPD1), but the protective actions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 58 publications
0
50
0
Order By: Relevance
“…The dysfunction or death of these cells are closely involved in sepsis-AKI (22)(23)(24). During the host's defense against infection, macrophages play a central role in innate immunity (25,26), recognizing pathogen-associated molecular patterns (PAMPs) and/or host-derived damage-associated molecular patterns (DAMPs) through pattern recognition receptors (27,28). PAMPs and/or DAMPs released from damaged tissues activate and promote the pro-inflammatory phenotype (M1) of macrophages, leading to the release of pro-inflammatory cytokines such as interleukin (IL)-1, IL-6, tumor necrosis factor-α (TNF-α), chemokines and reactive oxygen species (ROS), which cause damage to the kidney tissue (29,30).…”
Section: Macrophages Vascular Endothelial Cells and Renal Tubular Epithelial Cells Are Involved In Sepsis-akimentioning
confidence: 99%
“…The dysfunction or death of these cells are closely involved in sepsis-AKI (22)(23)(24). During the host's defense against infection, macrophages play a central role in innate immunity (25,26), recognizing pathogen-associated molecular patterns (PAMPs) and/or host-derived damage-associated molecular patterns (DAMPs) through pattern recognition receptors (27,28). PAMPs and/or DAMPs released from damaged tissues activate and promote the pro-inflammatory phenotype (M1) of macrophages, leading to the release of pro-inflammatory cytokines such as interleukin (IL)-1, IL-6, tumor necrosis factor-α (TNF-α), chemokines and reactive oxygen species (ROS), which cause damage to the kidney tissue (29,30).…”
Section: Macrophages Vascular Endothelial Cells and Renal Tubular Epithelial Cells Are Involved In Sepsis-akimentioning
confidence: 99%
“…Furthermore, previous studies reported a reduction of glial reaction upon local injection of PD 1 in mouse models of sciatic nerve transection, suggesting that the latter SPM might act through multiple pathways, yet to be fully understood (Xu et al, 2013). Consistently, GPR37 −/− mice display enhanced mechanical and cold allodynia, as well as thermal hyperalgesia during bacterial infections, while macrophages primed with GPR37 agonists reduce mechanical allodynia in the same GPR37 −/− mice (Bang et al, 2021). Also PD 1 has been demonstrated to counteract neuropathic pain by directly targeting sensory nociception via TRPV1 inhibition in DRG neurons (Park et al, 2011a), and by reversing nerve injuryinduced spinal cord synaptic plasticity in nerve trauma (Xu et al, 2013).…”
Section: Dha-derived Spmsmentioning
confidence: 96%
“…The innate behaviors of LPS-induce mice in automated home-cage monitoring should be carefully interpreted as behavioral pain since LPS was administered intraperitoneally. Although intraperitoneal administration of LPS has been devised in several pain models, such as sepsis-associated pain, musculoskeletal pain, and visceral pain [11,[18][19][20]35], the intraperitoneal administration of LPS can cause a systemic immune response leading to the development of sickness behaviors. Sickness behaviors produced by intraperitoneal administration of LPS include fatigue, depressive-like behavior, feeding behavior, anxiolytic-like behavior, changes in sleep-wake and feeding behaviors, weight loss, fever, and pain-like behaviors [8][9][10][11][12][13].…”
Section: Plos Onementioning
confidence: 99%
“…At the mechanistic levels both sickness and painlike behaviors are associated with increased pro-inflammatory mediators [8,17]. Therefore, the use of endotoxin has been recently introduced as a model for the study of inflammatory pain in both animals and humans [18][19][20][21][22][23][24][25]. The administration of LPS produces a significant expression of proinflammatory mediators, like cytokines, chemokines, cyclooxygenase-2 (COX-2), and nitric oxide through activation of toll-like receptor 4 (TLR4) via modulating immune cells [26][27][28].…”
Section: Introductionmentioning
confidence: 99%